Waste management in Dhaka City-A theoretical marketing model - Chowdhury, Tamzid Ahmed; Afza, Syeda Rownak (BRAC University, 2010)
An escalating quality of life and high rates of resources consumption patterns have had an unintended and negative impact on the urban environment generation of wastes far beyond the handling capacities of urban govt. and agencies. Cities are now grappling with the problems of high volumes of waste, the cost involved, the disposal technology and the impact of wastes on the local and government environment. Therefore, at this moment it is very much needed to make a proper plan for waste management and disposal system it has also been observed that waste can be another source for earning money. So, keeping this objective in mind, this study attempts to develop a proposed marketing model for waste management system in Dhaka city. It can also be considered as a preventive waste management approach, which is focused on changes in lifestyles and in production and consumption patterns. This article also tries to find out the commercial value of waste. Last but not least it is a proposal rather than a conclusive study. It needs a more pragmatic test for its reliability study